Impact of albuminuria on the various causes of death in diabetic patients: a nationwide population-based study - Cho, Semin; Huh, Hyuk; Park, Sehoon; Lee, Soojin; Jung, Sehyun; Kim, Minsang; Lee, Kyu-na; Paek, Jin Hyuk; Park, Woo Yeong; Jin, Kyubok; Han, Seungyeup; Joo, Kwon Wook; et al. (Scientific reports, 2023)
Diabetes mellitus (DM) is a well-known risk factor for mortality, and the risk is exacerbated by coexisting diabetic kidney disease (DKD). We aimed to explore the impact of DM on each cause of mortality according to kidney function and the presence of albuminuria. Data on subjects with DM were extracted from the Nationwide Health Insurance Database of South Korea between 2009 and 2012. Subjects were divided by eGFR and albuminuria into five groups. To evaluate the risk of diabetes, we used the Cox proportional hazards model. A total of 2,614,662 patients were enrolled in this study. Most causes of death showed a higher incidence in an advanced stage of DKD. In addition to all-cause mortality and cardiovascular death, the risk of death from neoplasms and diseases of the endocrine, respiratory, and digestive systems is increased by albuminuria. The synergistic effect of a reduced eGFR and the presence of albuminuria was prominent in death from circulatory diseases, and endocrine and metabolic diseases. The risk for mortality was different according to the stage of DKD. Even in patients with a favorable eGFR, the presence of albuminuria significantly increased the risk for mortality, especially that due to cardiovascular causes.